Insuficiencia jurídica del código orgánico integral penal, con relación a los agentes de inteligencia militar, puedan ser considerados como agentes encubiertos dentro de una investigación penal, necesidad de inserción. - Gaibor Avilés, Willians Estuardo (2018)
The Organic Code of Criminal Integral, Article 273, refers to the undercover agents, investigative activity that is in charge of the Attorney General, activity should perform based on the principle of necessity and with the support of staff specialized system Research Legal Medicine and Forensic Sciences, which includes members of the National Police of Ecuador and civilian personnel. Considering that the activities carried out by undercover agents, originate from special intelligence operations, who was born basically military intelligence, where military intelligence agents, are prepared to ensure the welfare and security of the State, as from their education are handled within the following concepts: Notwithstanding this, despite the high level of preparation available to military intelligence agents in the field of research in water, land and air spaces where their actions would be of great legal value, as they have special techniques and procedures to determine illicit activities, today's work FFAA it despite having their units Joint Military Intelligence, is not imbued with legitimacy and much less of legality, since the law does not authorize them to perform such work underground without authority this the command is a judge or prosecutor. Agents of Military Intelligence, when detecting illegal activities carried out by common criminal organizations and organized, proceed to ask the relevant judicial authorities, carry out the respective legal proceedings in this case correspond only under the legal figure of "Flagrancy" because intelligence activities as they are (monitoring, pursuits, photographs, films, audios etc.), in the case of military intelligence, were not ordered or approved by a prosecutor or judge, therefore do not have Legitimacy but if they are called to participate in the legal process of judging. Being within the legal process, the agents of Military Intelligence, are exposed to vulnerable conditions atentarían against the physical integrity and life, and that would be retaliated against, without taking into consideration the provisions of Article 273, the Organic code of Criminal Integral, which references and punishes the person who commits the crime of divulging identity of an undercover agent, informant, witness or protected person, but in the case of military intelligence agents, are not favored by this protection as they were not considered as undercover agents. Within the same Article 273 of the Code Integral Penal, which punishes anyone who improperly disclose the actual or new identity, address or whereabouts or other data to allow or give chance to other known information to identify and locate an undercover agent, informer, witness or protected person, the penalty is not exemplary, considering that the military intelligence agent and in some cases the undercover agent, informer, witness or protected person when he is discovered by criminal organizations to they are carried out covert operations usually are killed, why the penalty should be more drastic. The Public Safety Act and the State establishes the existence of the National Intelligence Secretariat in Ecuador, regulates all the actions of intelligence actions, gives guidelines for research on issues of public safety and state. Its mission is to ensure peaceful coexistence within the national territory and respect for national security areas such as borders or airspace. It is responsible for meeting the objectives of the National Intelligence System; Plan prepared by the National Intelligence and executes it. Ultimately, it is the body that carries out the decisions of the Council of Public Security and the State.